Pengaruh Motivasi Belajar, Computer Attitude Dan Fasilitas Laboraturium terhadap Prestasi Belajar Komputer Akuntansi - Oknaryana Oknaryana; Yulia Astuti; Khairi Murdy (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2020)
MYOB accounting computer is one of the subjects in vocational schools that learns about computerized accounting bookkeeping. Judging from the Mid-Semester Examination, there are still many students whose grades are below the Minimum Completion Criteria (KKM). In this study, it was examined whether learning motivation, computer attitude, and laboratory facilities affect learning achievement. The research sample was 66 students of class XI Accounting at SMK Negeri 1 Sawahlunto based on total sampling. Data collection techniques using questionnaires and documentation. The data analysis method used is multiple linear regression. The results showed that learning motivation, computer attitude, and laboratory facilities simultaneously influenced accounting computer learning achievement. While partial testing results show that learning motivation has a significant effect on accounting computer learning achievement with a significant value of 0,000. Computer attitude partially does not significantly influence accounting computer learning achievement with a significant value of 0.155. And laboratory facilities partially did not significantly influence accounting computer learning achievement with a significant value of 0.595